2012
DOI: 10.1007/s10654-012-9692-8
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional association between physical activity and symptoms of anxiety and depression: the Whitehall II study

Abstract: Although it has been hypothesized that the association of physical activity with depressive and anxiety symptoms is bidirectional, few studies have examined this issue in a prospective setting. We studied this bidirectional association using data on physical activity and symptoms of anxiety and depression at three points in time over 8 years. A total of 9,309 participants of the British Whitehall II prospective cohort study provided data on physical activity, anxiety and depression symptoms and 10 covariates a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

16
158
5
7

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(186 citation statements)
references
References 41 publications
16
158
5
7
Order By: Relevance
“…Consistent with prior work on individual health behaviors, 11, 13, 48, 49 results adjusting for relevant confounders indicated that every SD increase in anxiety or depression symptoms was associated with a significant decrease in the healthy lifestyle score over 20 years and with 12%–13% reduced odds of endorsing a healthy lifestyle at the end of follow-up, suggesting that even less severe symptoms may alter behaviors. Furthermore, women with higher versus lower levels of symptoms had a sustained unhealthier lifestyle score across time points and 21%–22% lower odds of reporting a healthy lifestyle 20 years later.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Consistent with prior work on individual health behaviors, 11, 13, 48, 49 results adjusting for relevant confounders indicated that every SD increase in anxiety or depression symptoms was associated with a significant decrease in the healthy lifestyle score over 20 years and with 12%–13% reduced odds of endorsing a healthy lifestyle at the end of follow-up, suggesting that even less severe symptoms may alter behaviors. Furthermore, women with higher versus lower levels of symptoms had a sustained unhealthier lifestyle score across time points and 21%–22% lower odds of reporting a healthy lifestyle 20 years later.…”
Section: Discussionsupporting
confidence: 79%
“…1018 For instance, in adults with initially low physical activity levels, higher anxiety and depression symptoms were related to 79% increased odds of being inactive 3 and 6 years later. 11 Other studies have demonstrated associations of anxiety and depression symptoms with subsequently developing excess adiposity and becoming obese 10, 13, 18 and with poor food choice, factors that may be used to cope with negative feelings. 19, 20 A recent meta-analysis showed clinical anxiety disorders were related to a 40% increased risk of becoming a regular smoker, 14 while women with moderate versus low levels of psychological symptoms had five fold increased odds of developing alcohol dependence problem over 18 months.…”
Section: Introductionmentioning
confidence: 99%
“…Regular engagement in a challenging activity may lead to an increase in a person's confidence and subsequently to a decrease in their depressive symptoms [39], or the social relationships developed from regular participation in physical activity may impact positively upon mental health [40]. Inversely, depression may negatively influence patterns of activity through symptoms such as low energy levels, apathy, or social isolation [41] or physical inactivity and depression and anxiety may also share other risk factors [38]. Our findings relating to the benefits of sport participation provide some support for the hypothesis that the mental health benefits of physical activity may be partly accounted for by the social interaction involved in team sports in particular, and confirm the importance of the psychological and social aspects of physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Lower rates of physical activity and increased sedentary behaviours are also commonly observed in currently obese (Bailey et al, 2007, Tucker andTucker, 2011) and psychiatric patients (Azevedo Da Silva et al, 2012, Song et al, 2012 and are also risk factors for the future development of both these conditions. Rates of sleep disorders such as insomnia and sleep apnoea are also increased in obesity and psychiatric disorders (Costa M A N U S C R I P T…”
Section: Possible Mediators Of the Relationship Between Obesity And Pmentioning
confidence: 99%